ABOUT THE STRATEGY OF IMPRESSING ENEMY UAVS - Bondar, O. P. (Systems and Technologies, 2022)
The article emphasizes that Ukraine is currently faced with an acute problem of protecting its state system, in connection with which the Armed Forces of Ukraine have to repel attacks, in particular, by enemy aircraft, an essential part of which is the use of unmanned aerial vehicles. The necessity of training qualified UAV operators, which, together with their acquisition of skills in practical control of the device, should include the tasks of theoretical substantiation of the strategy and tactics of UAV use is indicated. This means that the future operator of drones must be able to formalize the practical task set before him, know rational algorithms for its solution, acquire the skills of quick and optimal solution. A statistical analysis of the types and purpose of enemy drones shot down recently by the Armed Forces of Ukraine was carried out. The specified types of combat operations, as elements of the strategy of impressing or damaging enemy UAVs. Namely, we are considering combat operations aimed at impressing enemy UAVs primarily with our UAVs directly or in combination with the described means of destroying drones. It is noted that in combat conditions there are often tasks of destroying the enemy, in which the effectiveness of the combat operation is determined not by one, but by several indicators at once, some of which should be made larger, others smaller. For example, it is necessary to plan a combat operation in such a way that as a result, a maximum of enemy drones are destroyed with the greatest possible damage to them, and at the same time, so that a minimum of our objects are hit with the least losses. Tasks in which several goals must be achieved at the same time are called multi-objective or multi-criteria tasks. In such problems, the goals are usually incompatible – a decision that maximizes one indicator usually does not minimize the other. The concept of a multi-objective problem is considered and the algorithm of one of the methods of its solution is formulated – the method of successive concessions in combination with the method of expert evaluations. At the same time, each of the methods can be considered as a separate way of solving certain strategic problems. An example of the application of these methods in planning the strategy of impressing enemy UAVs is presented and solved. Since the statistics of military operations are currently being accumulated, it is emphasized that the statistical material should be regularly analyzed in order to train highly qualified UAV operators. The prospect of further research in this direction is a similar analysis that will allow us to determine the dynamics and patterns of changes in military operations, and, ultimately, will allow us to increase the effectiveness of the use of UAVs by our military in combat operations.